Knowledge, attitude, and practice of medical staff regarding problem based learning: experience of a Saudi Arabian university - Mustafa, Salah Mohamed; Abukanna, Abdelrahman Mohamed; Elnaeem, Kamal Mahmoud (International Journal of Research in Medical Sciences, 2018)
Background: Problem-based learning is an instructional approach that emphasizes inquiry. Problem-based learning was developed in the late 1960s and has been the most influential innovation in medical education during the past 50 years. Implementation of problem-based learning requires fundamental changes in the way educators conceive, design, deliver, and assess the curriculum. We designed this cross-sectional study to determine whether the staff members in the clinical years in the faculty of medicine in Northern Border University (NBU) has a previous experience with problem-based learning methods of teaching and to know their attitude towards it. Methods: Data were collected from 46 staff members in the clinical years of the faculty of medicine using hard copy questionnaire and analyzed using statistical package for social sciences software program. Results: The results showed that eighty percent of the clinical staff were graduated from colleges using the classical curriculum. Around 30% of them worked as PBL tutors before joining the faculty of medicine but all of them worked as PBL tutors after joining. Only one-third of the clinical staff know the steps of PBL when joining the faculty of medicine. Around 80% of study group think that hybrid curriculum is the best curriculum for faculties of medicine. Conclusions: The study group had the knowledge, practice, and experience of PBL method of teaching, they attended PBL workshops and like to attend more PBL workshops, in addition, the majority of faculty members think that the hybrid curriculum is the best for implementation in faculties of medicine.